Higher coated-platelet levels are associated with chronic hypertension in patients with transient ischemic attack. (June 2013) - Prodan, Calin I.; Vincent, Andrea S.; Dale, George L.
<x xml:space="preserve">Abstract</x> Coated-platelets are procoagulant platelets observed upon dual stimulation with collagen and thrombin. We previously reported that coated-platelet levels are elevated in patients with transient ischemic attack (TIA) compared to controls and that these levels correlate with ABCD2 scores, a validated tool for identifying the short-term risk for stroke occurrence in TIA patients. We now investigate the effect of individual elements of the ABCD2 score on coated-platelet levels in TIA. Coated-platelet levels were measured in 124 TIA patients. A nine-way ANOVA evaluated the impact of components of the ABCD2 score (age, blood pressure (BP), clinical features, symptom duration, and diabetes), smoking, pertinent medications, race, and gender on coated-platelet levels. In the initial model, the only significant main effect was for BP; patients with BP ≥ 140/90 had higher coated-platelet levels than those without (mean ± SEM; 44.0 ± 2.1% vs. 35.4 ± 2.3%, p = 0.0007). Because the diagnosis of hypertension (HTN) requires multiple readings of elevated BP, we re-analyzed the data by replacing BP with HTN. In the second model, there were two significant main effects: HTN – with higher coated-platelet levels in patients with vs. those without HTN (46.3 ± 2.1% vs. 33.6 ± 2.1%, p < 0.0001), and symptom duration – with higher coated-platelet levels in patients with duration ≥60 minutes vs. those with duration <60 minutes (42.5 ± 2.0% vs. 37.4 ± 2.1%, p = 0.031). These data suggest a link between chronic HTN and platelet thrombotic potential.